A 20‐gauge active needle design with thin‐film printed circuitry for interventional MRI at 0.55T. Issue 3 (16th April 2021) - Yildirim, Dursun Korel; Bruce, Christopher; Uzun, Dogangun; Rogers, Toby; O'Brien, Kendall; Ramasawmy, Rajiv; Campbell‐Washburn, Adrienne; Herzka, Daniel A.; Lederman, Robert J.; Kocaturk, Ozgur
Abstract : Purpose: This work aims to fabricate RF antenna components on metallic needle surfaces using biocompatible polyester tubing and conductive ink to develop an active interventional MRI needle for clinical use at 0.55 Tesla. Methods: A custom computer numeric control‐based conductive ink printing method was developed. Based on electromagnetic simulation results, thin‐film RF antennas were printed with conductive ink and used to fabricate a medical grade, 20‐gauge (0.87 mm outer diameter), 90‐mm long active interventional MRI needle. The MRI visibility performance of the active needle prototype was tested in vitro in 1 gel phantom and in vivo in 1 swine. A nearly identical active needle constructed using a 44 American Wire Gauge insulated copper wire‐wound RF receiver antenna was a comparator. The RF‐induced heating risk was evaluated in a gel phantom per American Society for Testing and Materials (ASTM) 2182‐19. Results: The active needle prototype with printed RF antenna was clearly visible both in vitro and in vivo under MRI. The maximum RF‐induced temperature rise of prototypes with printed RF antenna and insulated copper wire antenna after a 3.96 W/kg, 15 min. long scan were 1.64°C and 8.21°C, respectively. The increase in needle diameter was 98 µm and 264 µm for prototypes with printed RF antenna and copper wire‐wound antenna, respectively. Conclusion: The active needle prototype with conductive ink printed antenna provides distinct device visibility under MRI. Variations on the needle surface are mitigated compared to use of a 44 American Wire Gauge copper wire. RF‐induced heating tests support device RF safety under MRI. The proposed method enables fabrication of small diameter active interventional MRI devices having complex geometries, something previously difficult using conventional methods.